Prediction of spontaneous preterm delivery in singleton pregnancies: Where are we and where are we going? A review of literature. (August 2014) - Sananès, N.; Langer, B.; Gaudineau, A.; Kutnahorsky, R.; Aissi, G.; Fritz, G.; Boudier, E.; Viville, B.; Nisand, I.; Favre, R.
Abstract Prematurity is the chief cause of neonatal morbidity and mortality. The objective of this study is to review the different methods for predicting preterm delivery in asymptomatic pregnant women and in situations of threatened preterm delivery. A search of the PubMed/Medline database was carried out for the years 1980–2012. We included studies for predicting preterm birth in asymptomatic and symptomatic patients. Models for predicting preterm delivery based on maternal factors, cervical length and obstetric history in first trimester of pregnancy is a valuable avenue of research. Nevertheless, prediction accuracy still needs to be improved. In the second and third trimesters, routine digital vaginal examination is of no value in asymptomatic women. Echography of the cervix is not useful except in patients with a history of late miscarriage or preterm delivery in order to offer them a preventive treatment. In symptomatic women, the combination of digital vaginal examination, cervical echography and fibronectin gives the best predictive results. Electromyography of the uterus and elastography of the cervix are interesting avenues for future research. Identifying patients at risk of preterm delivery should be considered differently at each stage of pregnancy.